Intensive probation with young adult offenders - Brownlee, Ian (The British journal of criminology, 1995)
This paper describes briefly the results of an evaluation of one intensive supervision project in the north of England which was targeted at high tariff' young offenders. It discusses the diversion effect of the project and offers some assessment of the changes introduced by the Criminal Justice Act 1991 on this particular sentencing option. The main body of the paper reports the findings of a follow-up reconviction study of those young offenders who attended the Edge during its first 12 months of operation and compares their recorded reoffending with two samples from this age group who received custodial sentences for broadly similar offences. Finally, the possible implications of this study for the continued utility of intensive probation schemes is discussed in the wider contexts of penal polity and social justice